First record of Metatarsonemus (Acari: Tarsonemidae) from India with description of two new species - Mondal, Priyankar; Karmakar, Krishna (Zootaxa, 2021)
Two new species of Metatarsonemus Attiah, 1970 (Acari: Heterostigmatina: Tarsonemidae), M. badurkani Karmakar & Mondal sp. nov. and M. shirishi Karmakar & Mondal sp. nov., are described based on specimens collected from Ziziphus jujubae (Rhamnaceae), Lagerstroemia speciosa (Lythraceae), Piper betle (Piperaceae) and Albizia lebbeck (Leguminosae) in West Bengal, India. A larval description of M. shirishi and a dichotomous key to the species of Metatarsonemus are provided.